(untitled) (Journal of Partial Differential Equations, 2023)
This paper considers the Cauchy problem of the semilinear wave equations with small initial data in the Schwarzschild space-time, □_gu = |u_t | ^p , where g denotes the Schwarzschild metric. When 1< p